The African genus Taramassus: taxonomy, reproduction and stridulation (Saltatoria: Acrididae). - Schmidt, Gerhard Heinrich (Contributions to Entomology = Beiträge zur Entomologie, 1996)
The genus Taramassus and the six known species (cervus, cunctator, phyllocerus, platycerus, zavattarii and dirshi) are redescribed. For that, specimens of three species were collected in Somalia and Kenya and type material was available from five species. For T. platycerus the description of Uvarov (1953) was used. Comparative studies and differential analysis led to a key to the species. Rearing experiments were carried out successfully with T. cunctator: a pair was sufficient to establish a culture for comparative investigations. A new mode of sound production by the antennae is described in T. zavattarii. Keywords Taramassus species, redescription, key of the species, bionomy and reproduction of T. cunctator, mode of sound production in T. zavattarii.